Taxing Crime : A Whole-of-Government Approach to Fighting Corruption, Money Laundering, and Tax Crimes - Brun, Jean-Pierre (Washington, DC: World Bank, 2022)
Taxing Crime: A Whole-of-Government Approach to Fighting Corruption, Money Laundering, and Tax Crimes examines how tax audits and investigations can lead to uncovering white-collar crime and how investigations of corruption can, in turn, lead to prosecutions of tax evasion or recovery of unpaid taxes. Prepared jointly by the World Bank and the United Nations Office on Drugs and Crime (UNODC) Stolen Asset Recovery Initiative (StAR) and the Global Tax Policy Center at the Institute for Austrian and International Tax Law, Vienna University of Economics and Business, this report offers analysis, case studies, examples of legal and operational frameworks, and recommendations that policy makers can use to enhance cooperation between tax authorities and law enforcement agencies at the national and international levels.